Surgical treatment for complete ruptures of the rotator cuff - Strafun, Sergey; Dolgopolov, Olexey; Sergienko, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The work analyses results of the efficacy of the surgical treatment for ruptures of the shoulder rotator cuff. One hundred and twenty-six patients, who had ruptures of the rotator cuff, were operated on with help of the open, half-open and arthroscopic methods. The authors developed an algorithm for the surgical treatment in the above conditions. The clinical results were analysed by the activity of elevation, absence of pain in the shoulder region, and Constant score. Excellent results following the surgical treatment were obtained in 61 patients (55.4 %), good ones in 37 (33.6 %), and satisfactory ones in 12 (10.9 %). The results of the surgical treatment are comparable with those published by other authors.